PEMANFAATAN ANGKAK SEBAGAI PEWARNA ALAMI DAN ANTIOKSIDAN PADA SOSIS IKAN KEMBUNG (Rastrelliger kanagurta L.) - Pandiangan, Justicia Febi Estermaria; Putra, I Nengah Kencana; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
This research was conducted to identify the effect of adding angkak on the color, antioxidant content, change the number of TBA sausage for six days of storage, sensory’s characteristic of mackerel fish sausage, and to identify the right percentage to adds angkak can improve the color, antioxidant content, and change the number of TBA for six days of storage, and sensory’s characterisctic of mackerel fish sausage. The experimental design used was a completely randomized design (CRD). Treatment factor was consist of six concentrations: 0%, 0,5%, 1%, 1,5%, 2%, and 2,5%. Each treatment had three replications so that obtained 18 units of trial. Observations were made on intensity of colour, antioxidant capacity, number of TBA, and organoleptic characteristics (hedonic test and scoring test). Data were analyzed by One-Way Analysis of Variance at level of 1% and 5% and continued by Duncan. The addition of angkak has affected very significant on color intensity, antioxidant capacity, number of TBA, color, taste, and overall acceptance, also significant on texture of mackerel fish sausage. On the others hand, it has not affected on flavor of mackerel fish sausage. The right concentration is obtained from the use of 1 % angkak. It has L*’s score 31,71; a*’s score 21,10; b*’s score 21,13; antioxidant capacity 53,37 mg GAEAC/kg; number of TBA for the 6th day 0,31 g malonaldehide/kg, color rather faded red and rather liked, flavor rather liked, texture liked, taste bitter weak and liked, and overall acceptance liked.